WRITING SKILLS AT UNIVERSITY LEVEL - Dalibor Kesić; Tea Piršl; Danica Piršl (University of Banja Luka, Faculty of physical education and sport, 2011)
It is beyond questioning that out of all skills students say they want to strengthen, writing poses the biggest challenge. As students in western countries enter the university, writing almost always takes on a new and challenging dimension. As students leave their protected classrooms at the Gymnasium for the mass education settings at universities, they quickly realize that the demands placed on them also change just as drastically. Although some elements of the kind of writing required of students at the university are taught at the secondary schools, where they are mainly required to analyze texts and then to add their own opinions, students generally find that at university quite a different kind of writing is demanded of them than they have been prepared for. Students find they are required to navigate across a much more complex terrain than they had to at the secondary schools.